Effects of family life education in improving adolescents’ knowledge and attitude on reproductive health - Khan, Md. Iftakhar Hassan; Karim, Fazlul (BRAC Research and Evaluation Division (RED), 2019)
The study assessed the effects of Family Life Education meant for the Adolescents (AFLE) in improving their knowledge and attitude on the fundamental elements of reproductive health vis-a-vis explored their pattern of sharing about the learning with the peers, and identified further information needs on reproductive health. Data were collected from 444 adolescents through one to one interviews (148 with BRAC AFLE and 148 without BRAC AFLE, and 148 adolescents who had never been enrolled in schools). Adolescents from the BRAC school (296) were chosen by using multistage sampling method while the never school going adolescents (148) were selected conveniently. The study outcomes were compared between the three groups of adolescents mentioned above. Bivariate analysis showed that a majority of AFLE students had significantly higher correct knowledge on puberty (95.3%), menstruation (98.6%), marriage and pregnancy ·(99.3%), STD/AIDS (78.4%), and family planning (95.3%) compared to the adolescents without AFLE as well as those who never went school. Except in the case of correct age at first marriage of a girl, the adolescents with AFLE had higher level of satisfactory knowledge on most of the specific RH issues than those other two groups. In the logistic regression analysis, the AFLE appeared to be the strongest influential predictor, followed by the respondents' age, TV-exposure, radioexposure, and sharing of RH lessons with others. Thus, it appears that AFLE has played a positive role in improving rural adolescents' knowledge and attitude on RH issues. But it warrants addressing sex inequality and involving peers and family.